Bio- and nanotechnology as the key for clinical application of salivary peptide histatin: A necessary advance - Zambom, Carolina Reis [UNESP]; da Fonseca, Fauller Henrique [UNESP]; Garrido, Saulo Santesso [UNESP] (MDPI, 2020)
Candida albicans is a common microorganism of human’s microbiota and can be easily found in both respiratory and gastrointestinal tracts as well as in the genitourinary tract. Approximately 30% of people will be infected by C. albicans during their lifetime. Due to its easy adaptation, this microorganism started to present high resistance to antifungal agents which is associated with their indiscriminate use. There are several reports of adaptive mechanisms that this species can present. Some of them are intrinsic alteration in drug targets, secretion of extracellular enzymes to promote host protein degradation and efflux receptors that lead to a diminished action of common antifungal and host’s innate immune response. The current review aims to bring promising alternatives for the treatment of candidiasis caused mainly by C. albicans. One of these alternatives is the use of antifungal peptides (AFPs) from the Histatin family, like histatin-5. Besides that, our focus is to show how nanotechnology can allow the application of these peptides for treatment of this microorganism. In addition, our intention is to show the importance of nanoparticles (NPs) for this purpose, which may be essential in the near future.
Keywords: Antifungal peptides; Candida albicans; Histatin-5; Nanoparticles